2013
DOI: 10.1177/000313481307900613
|View full text |Cite
|
Sign up to set email alerts
|

Use, Cost, Complications, and Mortality of Robotic versus Nonrobotic General Surgery Procedures Based on a Nationwide Database

Abstract: Since its introduction in 1997, robotic surgery has overcome many limitations, including setup costs and surgeon training. The use of robotics in general surgery remains unknown. This study evaluates robotic-assisted procedures in general surgery by comparing characteristics with its nonrobotic (laparoscopic and open) counterparts. Weighted Healthcare Cost and Utilization Project Nationwide Inpatient Sample data (2008, 2009) were used to identify the top 12 procedures for robotic general surgery. Robotic cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 25 publications
0
44
0
Order By: Relevance
“…Robotic oesophagogastric surgery had a higher morbidity (9.4%) and mortality (0.3%) rate than laparoscopic surgery (7.1% and 0.17%, respectively, all P < 0.05). Cost was slightly higher for robotic oesophagogastric surgery (median $US42 358 versus laparoscopic $US40 441) …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Robotic oesophagogastric surgery had a higher morbidity (9.4%) and mortality (0.3%) rate than laparoscopic surgery (7.1% and 0.17%, respectively, all P < 0.05). Cost was slightly higher for robotic oesophagogastric surgery (median $US42 358 versus laparoscopic $US40 441) …”
Section: Resultsmentioning
confidence: 97%
“…Salman et al . reported on 37 270 robotic general surgery operations using discharge data from the Nationwide Inpatient Sample (NIS) for the January 2008 to December 2009 period . The NIS is a 20% stratified sample of US community hospital discharges collected by the US government's Agency for Healthcare Research and Quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The future of robotic surgery will also include improvements in haptic feedback and vision, and easier port placement and docking mechanisms. Even with the current robot, a study that used Nationwide Inpatient Sample data, representing 20% of US community hospital discharges, showed that the use of robotic general surgery in the operations selected increased from 0.8% in 2008 to 4.3% in 2009 . This study also reported that, overall, robot‐assisted general surgery was more cost‐effective than open or laparoscopic general surgery if hospitalization costs were included, and robotic general surgery was associated with lower morbidity and mortality.…”
Section: Discussionmentioning
confidence: 90%
“…This study also reported that, overall, robot‐assisted general surgery was more cost‐effective than open or laparoscopic general surgery if hospitalization costs were included, and robotic general surgery was associated with lower morbidity and mortality. This large study is subject to multiple potential confounders, including the likelihood that robotic surgery was typically used in less acute and less complicated procedures …”
Section: Discussionmentioning
confidence: 99%